MAGNETOSTRATIGRAPHY OF LOWER CAMBRIAN STRATA FROM THE SIBERIAN PLATFORM: A PALAEOMAGNETIC POLE AND A PRELIMINARY POLARITY TIME-SCALE - Rozanov A.Y.; Kirschvink J.L. (My University, 1984)
Four sedimentary sections seen in continuous exposures along the Lena River on the Siberian Platform in Yakutia contain a record of the geomagnetic field during the Tommotian and Atdabanian stages of Early Cambrian time. The direction of the stable remanent magnetization indicates that the Siberian platform was located on the equator, and the corresponding palaeomagnetic pole provides a well-dated extension of the Siberian apparent polar wander path. A belt of archaeocyathid bioherms which separates two major facies zones in the lower Cambrian was positioned on and aligned more or less parallel with the palaeoequator. The geographical position of this belt appears to have tracked the southward motion of the Siberian platform during post-Tommotian time. These palaeomagnetic results combined with the extensive biostratigraphy of the Siberian Platform provide a provisional geomagnetic polarity time scale for this part of Early Cambrian time. Comparison of these results with data of similar age from Central Australia suggests that strata of Tommotian and lower Atdabanian age are not present in the Amadeus Basin of Australia.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская